Low-molecular-weight transfer factor molecules improve the expression of CD2+ leukocytes in male finishing pigs - Posada, Ivan; Rubio, Maria del Rocio P. (Iraqi journal of veterinary sciences, 2026)
The small intestine is a major site of immune defense in pigs. Low-molecular-weight transfer factor (TF) molecules are known to play an essential role in regulating immune responses. This study aimed to investigate the effects of oral administration of TF on the expression of CD2+ leukocytes in the small intestine of male finishing pigs. Eighteen 18 male finishing pigs were randomly assigned to control, 300 mg/day TF, and 600 mg/day TF. TF was administered orally for 30 days. The expression of CD2+ leukocytes was determined by immunohistochemistry. Results showed that oral administration of TF significantly increased the expression of CD2+ leukocytes in the small intestine of pigs. The increase was observed in all three segments of the small intestine but was most pronounced in the ileum for 600 mg/day, with highly significant differences (P< 0.01, Duncan) and the response curves duodenum=1.2114/(1+3.7576e-6.4119x) CD2+ cells/mm2, jejunum=1.34258/(1+2.36566e-2.94002x) CD2+ cells/mm2, ileum=1.751185/(1+4.16359e-2.543x) CD2+ cells/mm2. Oral administration of transfer factor (TF) significantly increased the levels of CD2+ leukocytes in the duodenum, jejunum, and ileum of male finishing pigs. The increase was most pronounced in the ileum, with the 600 mg/day dose producing the greatest effect. These results suggest that oral administration of TF could be an effective strategy to improve small intestinal immune function in male pigs, especially at higher doses.